Zinc-biofortified wheat required only a medium rate of soil zinc application to attain the targets of zinc biofortification. Issue 4 (21st March 2021) - Yaseen, Muhammad Khalid; Hussain, Shahid
ABSTRACT: Zinc (Zn) deficiency is prevalent in human populations in developing countries. The present study compared two wheat ( Triticum aestivum L.) cultivars [Jauhar-2016 (standard wheat) and Zincol-2016 (Zn-biofortified wheat)] for Zn biofortification with optimum soil Zn application. For this, Zn (at 0, 3, 6, 12 and 24 mg Zn kg −1 ) was applied to pots having an alkaline calcareous soil. Grain yield, grain Zn concentration and grain Zn bioavailability in both cultivars were significantly increased by Zn fertilization. However, Zn application decreased iron (Fe) and phytate concentration in grains of both cultivars. As compared to Jauhar-2016, Zincol-2016 had significantly higher grain Zn concentration and grain Zn bioavailability at all the respective soil Zn rates excepting only at control. At 6 mg Zn kg −1, Zincol-2016 attained in grains a desired concentration of Zn (53 mg Zn kg −1 ) and a desired level of human Zn bioavailability (2.8 mg d −1 for women and was 3.0 mg d −1 for men). Jauhar-2016 also attained such comparative levels but only at a plant toxic rate of Zn (24 mg Zn kg −1 ). Conclusively, soil Zn application (agronomic biofortification) to Zn-biofortified wheat (Zincol-2016) may be a promising approach to decrease human Zn deficiency in population groups dependent on wheat-based diets.